Stability Study of Multicomponent Mixtures to Support Carbon Metrology - Dias Florbela A.; Palma Cristina; Costa Carlos J. (EPJ Web of Conferences)
The European project EPM SRT-v01 - MetCCUS (Metrology for Carbon Capture Utilization and Storage) is the first metrology project within the scope of CCUS (Carbon Capture Utilization and Storage), which, in the European ecological pact, European Commission’s Green Deal, is listed as one of the priority areas to achieve a reduction in greenhouse gas emissions by 55 % by 2030 and carbon neutrality by 2050. This project, financed by EURAMET, aims to respond to the metrological challenges identified by the industry and aims to provide the primary standards, methods, good practice guides that will support the necessary measurements. This study successfully characterized four bicomponent mixtures: SO2 in CO2 matrix (two mixtures) and H2S in CO2 matrix (two mixtures) and four multicomponent mixtures SO2+CO+O2 in CO2 (two mixtures) and H2S+CO+CH4+O2 in CO2 matrix (two mixtures) within a cylinder under a pressure of approximately 40 bar, and it entailed a stability study. The stability study was conducted over one year, employing statistical evaluation using the Normalized Error (En) function in accordance with the international standard ISO 13528:2022 for statistical methods.